PENGARUH PERLAKUAN PASCA PANEN DAN SUHU SIMPAN TERHADAP DAYA SIMPAN DAN KUALITAS BUAH MANGGA (Mangifera indica L.) VARIETAS ARUMANIS - Bambang S. Purwoko; Fera Santi Magdalena (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1999)
The objective of the experiment was to test the effectiveness of several postharvest treatments of mango at different storage temperatures. Mango cv. Arumanis at 80 % maturity was used in the experiment. A factorial experiment consisted of 2 factors was used. The two factors were storage temperature (24 - 25°C and 18 -19°C) and postharvest treatments (spermidine 1 mM; CaCl2 3 %, plastic wrapping, waxing, and control). Result of the experiment showed that plastic wrapping was the best in inhibiting weight loss, the increase of total soluble solid, ratio of TSS / acidity, the decrease of acidity. However; it also gave off-flavor. Storage at 18 -19°C was effective in inhibiting the increase of softening, total soluble solid, and the decrease of acidity